Thermal deviation mechanisms for coupled heat transfer between the combustion side and the furnace tube side in the tubular heating furnace - Liao, Feilong; Yan, Zhenrong; Li, Chuantao; Tao, Yao; Zhu, Shuixing (Applied thermal engineering, 2024)
•Heat transfer on the combustion side and tube side in a heating furnace is coupled.•Thermal loads’ effect on heating furnace’s thermal deviation is revealed.•Fuel gas hydrogen doping’s effect on thermal deviation is identified. Temperature deviation significantly affects the safe operation of tubular heating furnaces. This is attributed to the inevitable temperature difference between the flue gas and the working medium on the tube side. To date, little research has considered the dynamic heat transfer between the furnace body and the tubes in tube furnaces, and even less attention has been paid to the thermal deviation within tube furnaces. To optimize the operational parameters of the heating furnace, a comprehensive heat transfer model is established in this paper to numerically couple the heat transfer between the combustion side and the working medium on the tube side in tube furnaces. A hydrogenation feed heating furnace with a processing capacity of 600,000 tons per year in a chemical enterprise is selected as the subject of study. Using Fluent software, on the basis of coupled simulation, a non-uniformity coefficient of temperature distribution is introduced to characterize the thermal deviation within the furnace. The impact of the thermal load and hydrogen doping in the fuel gas on the thermal deviation within the furnace is analyzed. The numerical results demonstrate that with an increase in thermal load, the flame structure in the furnace gradually becomes concentrated, the average temperature of the flue gas increases, and the outlet temperature of the furnace chamber increases by 19%, with the thermal efficiency decreasing by 5.11%; at the same time, the overall non-uniformity coefficient of the temperature distribution in the furnace fluctuates irregularly, indicating a nonlinear relationship between the thermal load and the thermal deviation within the furnace. With an increase in the hydrogen content in the fuel gas, the flame structure in the furnace becomes more dispersed, the average temperature of the flue gas increases, but the combustion efficiency of the heating furnace exhibits irregular fluctuations; the thermal deviation within the furnace initially increases and then decreases, with a lower non-uniformity coefficient of temperature at 50% hydrogen content, which is 2.48% lower than at 40% hydrogen content. Under both conditions, the thermal deviation primarily leads to localized hot spots in the radiant furnace tubes and uneven temperature distribution in the convection section, with a minimal impact on the thermal efficiency of the heating furnace.